Gendered infidelity in comparative literary context - Elsehrawi, Magda (AUC Knowledge Fountain, 2012)
This thesis explores and explains the recurring presence of the adulterous female character in narratives from the medieval period to the modern, with reference to four narratives: The Arabian Nights and The Canterbury Tales by Geoffrey Chaucer from the medieval period, where there is a plentiful reservoir of tales about adulterous wives, as well as in the more recent novels of Lady Chatterley's Lover (1929) by the British novelist D. H. Lawrence, and A Certain Woman (2001) by the Egyptian novelist Hala El Badry, where the innate stream of thoughts of the contemporary adulterous wife and her struggles from a personal, social, and psychological aspects are represented. Through the exploration of these texts, this study seeks to go beyond stereotypes and question the standard view of the adulterous woman, by examining the reasons behind the act of adultery itself. Motivations for the adulteries are examined using diverse theoretical frameworks that cross various disciplinary borders and draw insights from literary criticism, psychoanalysis, philosophy, and gender studies. Given the broad historical and geographical contexts that this study covers, as well as the differences in fictional conventions, the lapse of time, and the developments in narrative genres, this thesis attempts to trace the evolutionary progress of the adulterous female character and the transformation of her image from the medieval tale to the modern novel. Instead of the flat condemnation evident in the older narratives, the contemporary adulteress is alternatively approached from within, where her feelings and the driving forces behind her adulteries are examined.